Prentice hall's federal tax 2010 : individuals - Pope, Thomas R.; Anderson, Kenneth E.; Kramer, John L. (Prentice Hall, 2010)
For any first course in Federal Taxation at the undergraduate or MBA level. The Pope/Anderson/Kramer series is unsurpassed in blending the technical content of the most recent federal taxation mandates with the highest level of readability and relevancy for students. The 2010 edition has been updated to include the American Recovery and Reinvestment Act of 2009